E-Module for CLIL with Augmented Reality in Dynamic Assessment to Increase EFL Writing Skill - Kristianto, Virgiawan Adi; Buntoro, Harijadi Gunawan; Handayani, Sri (Language Circle: Journal of Language and Literature, 2022)
Online learning becomes more challenging during pandemic as it requires instructional media or module which enable students to learn by themselves at home. Therefore, this study is aimed at investigating the effect of e-module with augmented reality used during dynamic assessment to improve students’ writing skills in content and language integrated learning class. This study employed quasi experimental approach with non – equivalent control group design. 66 students of Civil Engineering Department were involved as the samples of this study. Total sampling was used in this study. The students’ writings were then assessed using ESL composition profile rubric from Jacobs by two independent raters. The data from the raters were then analyzed using SPSS. The results t-test showed that there was significant difference on the average score of the post-test data on both groups and that between the average score of pretest and post – test scores on the experimental group.